Description of Mothers with Stunting Toddlers in Cikunir Village Singaparna Health Center, Tasikmalaya Regency In 2020 - Santi Susanti (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2021)
Stunting is one of the nutritional problems experienced by children under five years old (toddlers). The average prevalence of stunting under five in Indonesia in 2005-2017 was 36.4%. The Tasikmalaya Regency Health and Population Control Office recorded that the stunting rate until September 2019 reached 33.8%. The general objective of the study was to obtain an overview of the risk factors for pregnancy in mothers of stunting toddlers. The method used is a descriptive method. The research population was mothers of children under five stunting in the Cikunir village area in 2020. The sampling technique used total sampling. The number of research respondents was 46 respondents. The research data used primary data. Procedure for data collection by distributing questionnaires to respondents. Data analysis used univariate analysis. The results of the study found: (1) Mother's age during pregnancy was mostly in the healthy reproductive age range, namely 33 people (71.7%), (2) Antenatal Care mostly carried out pregnancy checks 4 times or according to the standard ANC visits, (3 ) History of pregnancy with mild anemia 15 people (32.6%). Conclusion. Maternal pregnancy history of stunting toddlers was found mostly in healthy reproductive age, most of the ANC were regular and a small part had risk factors for anemia in pregnancy. Suggestions for pregnant women should be regular ANC so that they can control the development of pregnancy and the fetus and consume Fe tablets of at least 90 tablets during pregnancy and eat a balanced diet